Effect of pollination modes on yield components in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Effect of different modes of pollination on yield parameters of Indian mustard showed that the maximum number of pods/plant, pod length, pod setting (%), number of seeds/pod, thousand seed weight, seed yield/ plot, seed germination (%), seed vigour and oil content (508.72 pods/plant, 5.69 cm, 86.32%, 15.66 seeds/pod, 6.87 g, 17.63 q/ha, 89.20%, 628.12 and 39.42%, respectively) were in open pollination followed by that in bee pollination (404.56 pods/plant, 4.92 cm, 78.33%, 14.26 seeds/pod, 6.39 g, 15.57 q/ha, 85.20%, 542.54 and 38.36%, respectively) and pollinators’ exclusion (287.56 pods/plant, 3.89 cm, 65.87%, 12.24 seeds/pod, 5.30 g, 13.01 q/ha, 78.40%, 385.54 and 37.04%, respectively). Seed yield increased by 35.50 and 19.66 per cent in open pollinated and Apis mellifera pollinated plots, respectively as compared to pollinators’ exclusion.